Two rare cases of bronchus‐associated lymphoid tissue lymphoma successfully treated with rituximab‐bendamustine. Issue 8 (6th August 2021) - Panitz, Nydia; Gerhardt, Kristin; Becker, Cornelia; Schleife, Hendrikje; Bach, Enrica; Opitz, Sabine; Schaudinn, Alexander; Platzbecker, Uwe; Kayser, Sabine
Abstract: BALT lymphoma is a rare B‐NHL with a favorable prognosis. We here report on two patients with nonspecific symptoms: one showed as major symptom severe thrombocytopenia and the other dyspnea and dry cough, thereby suggesting an inflammatory focus in the lungs. There is no standard of care established yet. Both patients were successfully treated with rituximab and bendamustine. Thus, combined immunochemotherapy should be considered as first‐line therapy as in other MALT lymphomas, if the treatment/eradication of an underlying chronic inflammatory disorder/trigger factor can be excluded. Abstract : BALT lymphoma is a rare B‐NHL with a favorable prognosis. We here report on two patients with nonspecific symptoms: one showed as major symptom severe thrombocytopenia and the other dyspnea and dry cough, thereby suggesting an inflammatory focus in the lungs. There is no standard of care established yet. Both patients were successfully treated with rituximab and bendamustine. Thus, combined immunochemotherapy should be considered as first‐line therapy as in other MALT lymphomas, if the treatment/eradication of an underlying chronic inflammatory disorder/trigger factor can be excluded.